PUBLIC SPEAKING BAGI REMAJA MASJID KELURAHAN TUAHMADANI KECAMATAN TUAH MADANI KOTA PEKANBARU - Afrinaldy Rustam; Mahyarni; Mahmuzar; Afrizal; Fahrurozi; Henni Indrayani; Astuti; Meflinda; Zulhaida; Meri Sandora; Ilham Chnadra Putra; Febru Dekmi Yeti; Rimet (Yayasan Wayan Marwan Pulungan, 2023)
This community service aims to improve public speaking skills for mosque youth in the Tuahmadani Village, Tuah Madani District, Pekanbaru City. Public speaking is an important skill for teenagers, because it can help them convey ideas, communicate effectively, and build self-confidence. The method used in this service is an intensive training approach. The service team will work with mosque administrators and young people to organize a series of public speaking trainings. The training materials will cover public speaking techniques, managing anxiety when speaking in front of a crowd, using the right body language, and how to compose and deliver a persuasive speech. The expected result of this service is an increase in public speaking skills for mosque youth in the Tuahmadani Village. With these skills, it is hoped that youth will be able to speak more confidently and effectively, and be able to convey positive messages to their peers and the surrounding community..